Copper nanoparticle polyvinyl alcohol-film with multimode fiber saturable absorber for Q-switched lasers - Ramli, Rizal; Mohd Yusoff, Norita; Sani, Abubakar; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Zan, Mohd Saiful Dzulkefly; Mahdi, Mohd Adzir (Academic Press, 2025)
We have demonstrated the utilization of copper nanoparticle polyvinyl alcohol film saturable absorber with typical single-mode fiber (CuNP/PVA-SMF-SA) and multimode fiber (CuNP/PVA-MMF-SA) in an erbium-doped fiber laser for the generation of Q-switched pulses. For both methods, the CuNP/PVA film was coated with an index-matching gel sandwiched between two fiber ferrules. By incorporating CuNP/PVA-based SA in a laser cavity, stable Q-switched pulses were attained with a pump power range of 31–92 mW vs. 49–215 mW, a repetition rate (maximum pump power) of 16.61 kHz vs. 33.90 kHz, and a pulse width (maximum pump power) of 24.40 µs vs. 12.95 µs for CuNP/PVA-SMF-SA and CuNP/PVA-MMF-SA, respectively. The primary advantage of the CuNP/PVA-MMF-SA is its broader Q-switched pulse operation range relative to its counterpart, attributed to its weaker light confinement effect resulting from a bigger core diameter. This device could sustain a higher injected penetration power at 31.6 mW, yielding an energy pulse of 94 nJ, which represents a 1.57 enhancement factor. This approach facilitates pulse energy upscaling by maximizing the oversaturation power limit without compromising the device's integrity. This will create new opportunities for high-energy Q-switched fiber laser applications in the photonics industry.